1970
DOI: 10.1126/science.167.3921.1119
|View full text |Cite
|
Sign up to set email alerts
|

Spectra of Backscattered Light from the Sea Obtained from Aircraft as a Measure of Chlorophyll Concentration

Abstract: Spectra of sun and skylight backscattered from the sea were obtained from a low-flying aircraft and were compared with measurements of chlorophyll concentration made from shipboard at the same localities and at nearly the same times. Increasing amounts of chlorophyll were found to be associated with a relative decrease in the blue portion of the spectra and an increase in the green. Anomalies in the spectra show that factors other than chlorophyll also affect the water color in some instances; these factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(81 citation statements)
references
References 7 publications
1
77
0
Order By: Relevance
“…Terrestrial ecosystems would also become less efficient at photon dissipation with less water in the global water cycle. Incident angle and frequency dependent albedo for sunlight on ocean water of today has been measured by Clarke et al (1970) and Jin et al (2004). They find that organic material in ocean water reduces the albedo at all incident angles and wavelengths and that this effect increases significantly towards the shorter wavelengths of the ultraviolet.…”
Section: The Sea-surface and Entropy Productionmentioning
confidence: 99%
“…Terrestrial ecosystems would also become less efficient at photon dissipation with less water in the global water cycle. Incident angle and frequency dependent albedo for sunlight on ocean water of today has been measured by Clarke et al (1970) and Jin et al (2004). They find that organic material in ocean water reduces the albedo at all incident angles and wavelengths and that this effect increases significantly towards the shorter wavelengths of the ultraviolet.…”
Section: The Sea-surface and Entropy Productionmentioning
confidence: 99%
“…By absorbing and dissipating UV and visible light on the surface of oceans and lakes, life therefore augments the entropy production of the Earth in its solar environment. Without life at the surface, a greater portion of light would be reflected, increasing the albedo of Earth (Clarke et al, 1970, give measurements for the reduction of water albedo at different frequencies due to the presence of organic material), and light would penetrate deeper into the ocean, thereby augmenting the overall bulk black-body temperature of the ocean (see, for example, Jones et al, 2005 for the effect of phytoplankton on the temperature profile with depth for a lake). Both effects reduce the entropy production of Earth; greater albedo reduces the amount of available light to dissipate, and penetration of light to greater depth shifts the radiated spectrum (day + night integrated) to shorter wavelengths (see Eq.…”
Section: Entropy Production Due To Life In the Ocean Surface Layermentioning
confidence: 99%
“…6 This followed on from the work of Clarke et al 7 who showed that chlorophyll concentration in the ocean surface waters could be estimated from airborne measurements of the light leaving the sea surface. CZCS made measurements in four channels in the visible part of the spectrum, one channel in the near-infrared, and one in the infrared (IR) (see Table 2 for details of the sensor).…”
Section: A Brief History Of Ocean Color Measurements From Spacementioning
confidence: 99%